Techniques for Handling Challenging Student Behaviour in Language Learning Classrooms - Hasanov, Mahammad (Jaunųjų mokslininkų darbai, 2025)
Despite the numerous studies conducted on the positive discipline techniques in addressing misbehaviour in the classroom, a significant gap remains in our understanding of how these challenges and their associated techniques differ based on the specific classroom environment and the subject. This article aims to identify the common causes of misbehaviours in the foreign language classrooms and teachers’ response and techniques to deal with these challenges by maintaining positive discipline. The present study was conducted in the context of a workshop that involved eight foreign language teachers at a private school. The workshop was discussion based, and participants shared their challenges and techniques to deal with them accordingly. The research methodology applied was qualitative, with content analysis and the usage of inductive coding to analyse the data gathered from the workshop. The findings of the study indicate that the most prevalent causes of problematic behaviour in foreign language classrooms are academic challenges, attention seeking, and individual needs. The strategies employed to address these challenges include active engagement, personal talks, positive reinforcement, and classroom rules reminders.
Keywords: Positive discipline techniques; foreign language classroom; causes of misbehaviour; teacher responses; classroom management